Principles and rules: the open question argument and normative imperatives. (4th September 2009) - Arthur, Alex
The 'rules vs. principles' debate reappearing in the accounting literature has parallels in many disciplines and thematic links to many more. The purpose of this paper is to consider some of these links and to suggest an explanatory taxonomy based on the 'open question argument' drawn from analytic philosophy and some distinctions made by algorithmic theorists. This framework helps to explain some empirical findings and, perhaps, lends credibility to professional preconceptions (Institute of Chartered Accountants of Scotland, 2006).